Feminist Perspective towards the Legal Theory on Fisher-Women’s Legal Entity - Rima Vien permata Hartanto; Adi Sulistiyono; Isharyanto Isharyanto (Universitas Lampung, 2019)
This research explores the issue of the legal entity for fisher-women. Feminists Legal Theory is the main foundation. This theory seeks to criticise and dismantle the law by questioning the existence of laws that bring injustice to women's groups. In the Indonesian context, where the influence of patriarchal ideology and legal positivism theory is still active, the view that the law is believed to be neutral and objective has resulted in many things that discriminate and marginalise women's groups. This research presents the criticism of Law Number 7 of 2016 concerning the Protection and Empowerment of Fishermen, Fish Cultivators and Salt Cultivators for the recognition of the legal entity of fisher-women. This research is theoretical with the type of literature study focusing on ideas using a feminist perspective research approach. The results of the study indicates the that Law Number 7 of 2016 concerning the Protection and Empowerment of Fishermen, Fish Cultivators and Salt Farmers contains many weaknesses. There is a prejudice towards the work of fishers, there is a problem defining fishers because women are excluded from defining fishers, the absence of recognition of fisher-women affects the law and becomes indirect discrimination because of gender blindness and does not take into account in terms of women's experience or interests.